(untitled) (Journal of Economic Research & Business Administration, 2016)
The Republic of Kazakhstan has high potential for tourism, still, in the ranking of countries by the Index of competitiveness of the travel and tourism sector in 2013 (Travel and Tourism Competitiveness Index 2013), published by the World Economic Forum [1] as well as the World Bank’s ranking of Logistics Performance Index (LPI) in 2014 [2] it took only 88th place. Therewith, the main factor holding back the development of tourism, both in the country and in the regions, is still undeveloped tourist infrastructure, low rates of development and improvement of its basic elements in particular. The article describes the approaches to the formation of tourist infrastructure at recreational areas and the major factors affecting the tourist activity of the population, which allowed to establish the main problems hindering the development of tourist infrastructure as well as to formulate directions for its improvement.